ANALISIS PERBANDINGAN METODE SAW DAN TOPSIS PADA SISTEM PENDUKUNG KEPUTUSAN RUMAH KOST DI WILAYAH CIKANDE - Nida Nur Hasanah; Bambang Wisnu Widagdo (JUPIK : Jurnal Penelitian Ilmu komputer, 2024)
Boarding house is a service that offers a room or place to stay for a certain amount of payment for each certain period (generally monthly payments). The difficulty in choosing a place to live, especially in the Cikande area, means that people have to be careful in choosing what they want according to the criteria. Developments at the scene show that when choosing a temporary residence (boarding house), there are five aspects that are at least taken into consideration, namely: price, cleanliness, facilities, area and distance. In this research, 2 methods were used for comparison, namely the Simple Additive Weighting (SAW) method and the Technique For Order Preference By Similarity to the Ideal Solution (TOPSIS) IN THE BEST BOARDING HOUSE DECISION SUPPORT SYSTEM IN THE CIKANDE REGION which aims to provide solutions to the community in searching for a residence that suits your wishes and is easy to understand and has the ability to measure the relative performance of alternatives because the evaluation in ranking is based on predetermined criteria values ​​and weights. A website-based system using the PHP (Hypertext Preprocessor) programming language and MySQL as the database. It is hoped that the results of this research can help the public in making it easier to find a boarding house that suits their wishes.